(untitled) (Washington, DC, 2007)
International migration has become a central element of international relations and global integration due to its rapidly increasing economic, social, and cultural impact in both source and destination countries. This book provides new evidence on the impact of migration and remittances on several development indicators, including innovative thinking about the nexus between migration and birth rates. In addition, the book identifies the effect of host country policies on migration flows, examines the determinants of return and repeat migration, and explores the degree of success of return migrants upon return to their country of origin.
Keywords: Emigration and immigration,Di cư và nhập cư,Emigration and immigration,Emigrant remittances; Khía cạnh kinh tế,Economic aspects